Analisa Perencanaan Pembayaran Menggunakan Sistem QR Code di Industrial Universitas Advent Indonesia - Santa Frita Saragih; Elmor Benedict Wagiu (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2019)
Currently the payment systems in the Industrial of Universitas Advent Indonesia uses cash and the financial records are done manually. There are some problems occur because of the sales financial records are still manually recorded on the book and after that the book will be given to the Academic Finance Bureau (BAK) as the prove of report. This study aims to provide an overview of the new payment system, it is electronic payments by using the QR Code as a solution to overcome the manual financial recording problems and to find out the readiness of the users, they are the students, lecturers and staffs regarding the new payment system. The method used in data collection were interview, survey and observation, questionnaire and literature studies. The modeling used in this study to design a new system that was UML (Unified Modeling Language) and a questionnaire to determine the readiness of users. The conclusions of this study were 1) With this system, it can prevent errors at the income calculation because the calculations are no longer done manually, 2) With this system, forgetting to record sales results can be solved because the recording is done directly or realtime in the system, 3) With this system, no need to buy books to record the sales because everything is recorded in the system, 4) Financial supervision will be easily to be controlled, 5) Searching and inspection of data is easy and quick, 6) The Industrial of Universitas Advent Indonesia no need to provide sales report to BAK because the sales report can be directly accessed by BAK in the system, 7) Based on the results of the questionnaire that has been collected and processed, the overall average answer of the respondents from the 10 questions provided are agreed. It can be concluded that the user is ready for the electronic payment system in the Industrial of Universitas Advent Indonesia. Keywords: QR Code, Electronic Payment System, UML, BPMN